Linearization approach to partial differential equations - ARBIA, Abdelkrim; ZAOUCHE, Ismail (Université of eloued جامعة الوادي, 2025)
In this memory, we explore the application of the linearization technique in some nonlinear elliptic problems. We use this approach together with the fixed point theorem to prove the existence of nontrivial weak solutions to certain nonlinear elliptic problems. Résumé Dans cette mémoire, nous explorons l’application de la technique de linéarisation dans certains problèmes elliptiques non linéaires. Nous utilisons cette approche conjointement avec le théorème du point fixe pour prouver l’existence de solutions faibles non triviales à certains problèmes elliptiques non linéaires.
Fundamental and Applied Mathematics
Keywords: linearization; nonlinear elliptic problems; fixed point theorem; existence.; linéarisation; problèmes elliptiques non linéaires; théorème du point fixe